Prestroke treatment with beta-blockers for hypertension is not associated with severity and poor outcome in patients with ischemic stroke: data from a national stroke registry. Issue 4 (April 2017) - Koton, Silvia; Tanne, David; Grossman, Ehud
Abstract : Background: Beta-blockers are not recommended as the initial therapy for hypertension. Reports on associations between use of beta-blockers and stroke severity are inconclusive. We assessed associations between prestroke use of beta-blockers and stroke severity, poststroke disability and death in a large group of hypertensive patients hospitalized with acute ischemic stroke. Methods: All 3915 patients with ischemic stroke, treated prestroke for hypertension and registered in the National Acute Stroke ISraeli, were included. Treatment for hypertension was classified by medication type (beta-blockers, diuretics, calcium antagonists and renin–angiotensin system blockers). Odds ratios for stroke severity by the National Institutes of Health Stroke Scale score, disability or death at discharge (modified Rankin Score ≥2) and 1-month mortality were calculated for patients treated vs. nontreated with beta-blockers, adjusted for admission SBP and additional risk factors. Results: Use of beta-blockers was reported for 2043 (52%) participants. Mean (SD) admission SBP was lower in patients treated than nontreated with beta-blockers [156.7 (28.4) vs. 159.9 (27.8) mmHg; P = 0.0005]. Patients on combination therapy including beta-blockers used more antihypertensive medications than patients on combination therapy not including beta-blockers [mean (SD) = 2.63 (0.70) vs. mean (SD) = 2.17 (0.40); P < 0.0001]. Adjusted odds ratios (95% confidence intervals) for outcomes for beta-blocker users compared with nonusers were 1.09 (0.90–1.32) for severe stroke, 0.87 (0.73–1.03) for disability or death at discharge and 0.99 (0.74–1.31) for 1-month mortality. Findings were similar for patients on monotherapy. Conclusion: Prestroke use of beta-blockers in hypertensive patients with acute ischemic stroke was not associated with stroke severity, functional outcome or death. Abstract : Supplemental Digital Content is available in the text